Reaksi Pasar Terhadap Pengumuman Dividen Perusahaan Yang Termasuk Kategori LQ 45 - Wahyuni, Putu Ayu Sri; SUKARTHA, I MADE (E-Jurnal Akuntansi; Vol 2 No 1 (2013), 2013)
This study aimed to examine the information content of dividend announcements that can be measured by the market reaction occurs. The market reaction can be measured by abnormal stock return and trading volume. Using the event study approach with a 10-day observation period. To calculate the return ekspektasian using Market Model. Sampling method used was purposive sampling method in order to get a sample of 36 companies. Statistical test equipment used was paired sample t-test and one-sample t-test. The results obtained by the analysis there is no market reaction to the dividend announcement event. There is no positive market reaction to the companies that announced dividend increases. There are no negative market reaction to the companies that announced dividend decreases. There was no difference in reaction arising from the announcement of dividend increase announcements of dividend decreases company category LQ 45 in 2011.   Key words : abnormal return, market reaction, trading volume